The effects of foreign direct investments on export performance in Central Asian countries - A. Syzdykova; K. Massadikov (Хабаршысы. Экономика сериясы, 2022)
It is recognized in the economic literature that foreign direct investment (FDI) has many potential impacts on countries. These include; FDI’s capital, production and management knowledge will bring new technologies, increase competitiveness and productivity in the national industry, increase the amount of low-cost and high-quality products, facilitate trade in goods and services, positively affect export performance, accelerate economic growth and positively contribute to employment. It can be deemed to contribute. For this reason, countries try to attract investment from foreign countries by improving the investment climate in order to benefit from foreign direct investments. In this context, Central Asian countries (Kazakhstan, Kyrgyz Republic, Turkmenistan, Tajikistan and Uzbekistan) have started to implement various reforms and incentive policies to attract foreign capital after gaining their independence. The main purpose of this study is to investigate the effect of foreign direct investments directed towards Central Asian countries on exports, with reference to the effects of foreign direct investments on international trade. For this purpose, it has been tested with the panel data method using the quarter data of the Central Asian countries for the period 2000-2019. The study is expected to contribute to the economics literature on Central Asian countries. Key words: foreign direct investment, Central Asian countries, exports, panel data analysis.